Analisis Pengaruh Sikap, Norma Subjektif dan Kontrol Perilaku Terhadap Minat Pelaku UMKM Untuk Menyusun Laporan Keuangan : Sebuah Bukti Empiris Dari UMKM di Kota Ambon: Kata Kunci: Sikap, Norma Subjektif, Kontrol Pengaruh Perilaku, Minat Pelaku UMKM, Laporan Keuangan - Grace Persulessy; Pieter Leunupun; Marthen Jacob Leunupun (Jurnal Akuntansi, 2020)
The purpose of this research is to determine the effect of attitudes, subjective norms, and behavioral control on interest in compiling financial reports on micro, small and medium (UMKM) actors. This research uses regression analysis with a sample of 186 UMKM actors. The results of the study found that attitudes, subjective norms and behavioral control had a positive and significant effect on the interest in preparing financial statements for UMKM players in Ambon city. The results of this study contribute to providing empirical evidence about factors that can influence interest in preparing financial statements.